Tragedi Terorisme di Indonesia sebagai Bentuk Evolusi Ancaman Keamanan Nasional Tahun 2000- 2010, Pendekatan Fenomenologi - Fathun, Laode Muhamad (Jurnal Keamanan Nasional, 2021)
This article aims to explore the tragedy of terrorism in Indonesia from 2000-2010 as a threat to the evolution of global security. This paper uses a qualitative paradigm with a phenomenological method. The secondary data source used data collection techniques by means of interview transcripts between Ali Imron and ILC TV One. The results obtained are, based on the narrative of Ali Imron, it is stated that the incidents of terrorism in Indonesia are affiliated with two terrorist organizations, namely Al Qaeda and ISIS. In general, the purpose of terrorist acts is because a) as a form of creating an Islamic State and can only be carried out by the method of jihad and b) the obligations of the Shari’a, namely as a mujahid which resulted in martyrdom. As for the actions that occurred from 2000-2010 for reasons a) jihad b) revenge. In addition, ideology is divided into takfiri and fasikun ideologies. Therefore, the solution must use a collaborative and coordinating method involving all stakeholders.